The State of Research on PD1/PD-L1 Regulation by Non-coding RNA in Non-small Cell Lung Cancer - Fan, Ruohan (International Journal of Public Health and Medical Research, 2024)
Globally, non-small cell lung cancer (NSCLC) is the primary cause of death from cancer. Immunotherapy has advanced significantly in the medical management of NSCLC over the previous couple of decades. Particularly immune checkpoint drugs that target programmed death receptor 1 (PD-1) and its ligand 1 (PD-L1). Meanwhile, miRNAs are crucial for controlling the PD-1/PD-L1 pathway in NSCLC and are an increasingly significant field of investigation at the moment. For these reasons, this paper reviewed the mechanism of the PD-1/PD-L1 pathway in immunological escape from malignant cells and explored how non-coding RNAs (including microRNAs, long-chain non-coding RNAs, and cyclic RNAs) can affect the occurrence as well as growth of NSCLC by regulating PD-1/PD-L1 activity. Argument cites specific miRNAs such as miRNA-200c have the capability to alter the level of PD-L1 expression and thus enhance cancer innate immunity. Beyond that, LncRNA such as NEAT1 affect expression of PD-L1 and evasion of the body's defenses through interaction with miRNAs. In NSCLC, circular RNAs are performing a crucial function in evading immune responses. The article also discusses the efficacy and challenges of our self-developed PD-1 inhibitors in treating advanced NSCLC and emphasizes the need to improve the precision of immunotherapy. Finally, the article highlights the necessity for additional investigation to uncover more upstream modulators to enhance the prognosis and clinical outcomes of NSCLC individuals.